De que padecem as mulheres? o (in) suportável do sofrimento - Corso, Maria das Graças Ramos Del (2015)
The course of this work stemmed from clinical experiences and focuses on reports of women who become ill and offer themselves in sacrifice, reissuing malaises resulted from libidinal excesses that mobilize them, which, in a certain sense, evoke the question of how the morbidity of such state of suffering provides them with a special place in relation to the Other. The objective of this research was to investigate psychic subsidies that support this type of operation, as well as to consider the subjective effects of the maternal figure in these women s adult lives. To this end, we find in the Lacanian concept of jouissance, extracted from the Freudian notion of death drive, the theoretical resource with which we can move towards the modalities of feminine jouissance. The perspective adopted here combines relevant topics that are intertwined so as to turn paradigmatic the operation of aspects in the instinctual body that may be involved when we think about the conditions of the subject s ex(s)istence through an approach focused on the quantum formulas about sexualization, on the enigma of sexual difference, and on the transmission of this legacy whose foundation is based on the Real, which radically changes the perspective of direction of the analytic treatment